An exploratory examination of executive functioning as an outcome, moderator, and predictor in outpatient treatment for adults with anorexia nervosa - Ella Keegan; Susan Byrne; Phillipa Hay; Stephen Touyz; Janet Treasure; Ulrike Schmidt; Virginia V. W. McIntosh; Tracey D. Wade (Journal of Eating Disorders, 2022)
Plain English Summary People with anorexia nervosa often have difficulty thinking flexibly and in terms of the big picture. We investigated whether these thinking styles (1) change over treatment, (2) influence response to treatment, or (3) predict whether people gain weight or overcome the eating disorder. We found that people were able to think more flexibly after treatment. We also found that people who had more difficulty seeing the big picture prior to treatment had a more rapid decrease in eating disorder symptoms and clinical impairment in treatment. Thinking styles did not predict whether people gained weight early in treatment or overcame the eating disorder. Our findings suggest that the detail-focused thinking style commonly observed among people with anorexia nervosa can be both a vulnerability and a strength.